Paving the way for rural revitalization: Empirical analysis of the ‘Sihao Rural Road Policy’ and transport mode choice in Inner Mongolia, China - Yintu Bao; Gumula Wuri; Dan Shan; Ligao Bao (PLoS ONE, 2025)
This study investigates the impact of the Sihao Rural Road (SHRR) Program on travel behavior in Qingshuihe County, Inner Mongolia, China focusing on travel mode choice, travel frequency, and travel distance. Using an integrated Structural Equation Model (SEM) and Discrete Choice Model (DCM) framework, data were collected from 127 households between August 2023 and March 2024. The analysis reveals that the SHRR program significantly reduces travel frequency, likely due to improved local accessibility that decreases the need for frequent trips. Simultaneously, SHRR facilitates longer travel distances and promotes greater reliance on motorized modes. This suggests that enhanced infrastructure enables residents to travel farther and more efficiently using private vehicles, motorcycles, and electric bicycles. Car ownership plays a critical role, significantly influencing both travel distance and the adoption of motorized modes. However, its relationship with the use of electric bicycles is more complex, with effects mediated by other factors such as travel distance and frequency. These findings underscore the importance of considering both direct and indirect effects of rural infrastructure policies when evaluating their impact on mobility patterns and transport mode choices.